The Indispensable Liabilities of Leaders in Times of Covid-19 Pandemic - Ali, Mazhar; Anum, Zarmeena; Nasir, Anam; Ahmad , Nazir (South Asian Journal of Social Sciences and Humanities, 2021)
This explanatory paper seeks to examine domestic and international competences of world leaders towards the organizations in COVID-19. In this crisis phase, the organization empowers leader’s critical competences to survive in the crucial business environment. The role of leaders in this Pandemic ramification is exclusively meticulous. The particular research question that drives this work is: what leadership skills are needed during crises? And what is it? What are the critical competences which help their organizations during and post-crisis? In this manuscript, we have some literature-based descriptions from foreign and domestic perspectives as necessary competences for leadership activities a worldwide epidemic. We discussed leadership skills needed in period of disasters, accompanied by discussing best practices leadership in various ways and new reflections for top management analysts and professionals post a financial crisis. This study highlights and extends a few appropriate leadership qualities and competences which are highly useful for all the current leaders and organizations.